Evaluation of Genetic Divergence in Snakegourd (Trichosanthes anguina) - Sanju Susan mathew (Department of Plant Breeding and Genetics, College of Agriculture, 1996)
A set of 34 genetically diverse lines of snakegourd from different agro-ecological regions of the country were evaluated in a Randomised Block Design with two replications in the Department of Plant Breeding and Genetics, College of Agriculture, Vellayani during 1994-'96. This study was undertaken to estimates the extent of genetic diversity in the population of snakegourd genotypes so as to select suitable parents for use in heterosis breeding. Genetic parameters, association among the characters, direct and indirect effect of characters on yield and D2 values were estimated. The genetypes were significantly different for all the quantitative characters studied. The phenotypic and genetypic variances were almost equal for most of the characters. High genotype (GCV) and phenotypic (PCV) co-efficients of variation were observed for mean fruit weight, number of seeds per fruit, fruit yield per plant and fruit length. GCV was maximum for mean fruit weight and minimum for flesh thickness. High heritablity coupled with high genetic advance was observed for mean weight, number of seeds per fruit, fruit length and fruit yield per plant. Yield per plant was positively associated with all the characters except number of fruits per plant at the genotypic and phenotypic level. Path analysis revealed that flesh thickness, days to first female flower and mean fruit weight were the primary yield contributors in snakegourd owing to their high positive direct effect on yield. Selection indices for improvement of yield, therefore, should be based on heavier fruits with thicker flesh. Mahalanobis D2 analysis clustered the 34 genotypes into nine group constellations with genotypes from different eco-geographic locations being grouped in the same cluster. The clustering pattern indicated that geographic diversity need not necessarily be related to genetic diversity. The genetic distance was maximum between Clusters V and VII and minimum between Clusters IV and VI. Cluster III had the highest intracluster distance. Clusters IV, V, VI, VII, VIII and IX had only one genotype each. The characters viz., days to first female flower followed by duration of the crop, days to first fruit harvest and 100-seed weight contributed maximum towards genetic divergence. In fututre breeding programmes, selection of parents from Cluster V and VII for hybridisation is likely to give the most heterotic hybrids.